SUPERVISION OF LEGALLY REGISTERED COOPERATIVES AND SAVINGS AND LOAN COOPERATIVES INCLUDES MICROFINANCE INSTITUTIONS PERSPECTIVE - Joseline; Yudhi Priyo Amboro; Lu Sudirman (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Savings and loan cooperatives, which form the nucleus of the populace's economy, are not solely based on the kinship basis. As stated in the UUD 45's and the Cooperative Law's mandate, the supervisory function must be carried out optimally in order to serve the larger community because the sustainability of the national economy is heavily influenced by the expediency principle. This study employs a legislative approach and a qualitative analytical method in its descriptive analysis. In this study, it is discussed how to supervise KLM, a cooperative legal organization, following the implementation of UUP2SK, as well as how to supervise savings and loan cooperatives following the passage of UUP2SK. Based on these issues, it is known that: (1) The emergence of Microfinance Institutions with the legal status of cooperatives makes it necessary to pay closer attention and distinguish between cooperatives that are open loop & close loop in order to prevent similar cases from spreading to the larger community; (2) OJK as the authority given the mandate by the UUP2SK to guide and supervise the business operations of Savings and Loans Cooperatives over When creating derivative regulations for additional measures for licensing, regulation, and supervision of Savings and Loans Cooperatives, the goal is to avoid being easily seduced by phony investments with high interest rates.